Antioxidant response and oxidative stress levels in Macrobrachium borellii (Crustacea: Palaemonidae) exposed to the water-soluble fraction of petroleum - Lavarias, Sabrina Maria Luisa (2011)
The aim of the present work was to evaluate the effect of the water soluble fraction of hydrocarbons (WSF) on the antioxidant status of the freshwater prawn Macrobrachium borellii. First, seasonal variations were studied in a non-polluted area. Hepatopancreas and gills showed season-related fluctuations in catalase (CAT), glutathione-S-transferase (GST) activities and in lipid peroxidation levels (LPO), but not in superoxide dismutase (SOD). Then, adults were exposed semi-statically to sublethal doses for 7 days. CAT, SOD, GST, and glutathione peroxidase (GPx) activities and LPO, reduced glutathione (GSH) and protein oxidation (PO) levels were determined. Exposed individuals showed significant increases in CAT, SOD, and GST activities in hepatopancreas and CAT activity in gills. GPx activity did not vary in either tissues. While LPO levels increased, GSH levels decreased significantly in hepatopancreas of exposed animals, but PO levels showed no variation. Induction of SOD was also assessed by Real-time PCR mRNA expression in hepatopancreas. The nonenzymatic antioxidant activity was also tested; ABTS 2,2′-azino-bis(3-ethyl-  benzothiazoline-6-sulfonic acid) was higher in hemolymph of treated-prawns compared to controls, but ferric reducing activity of plasma assay (FRAP) values did not change. Taken together, the present results indicated that the antioxidant defenses of M. borellii, mainly in hepatopancreas, were significantly affected by aquatic hydrocarbon contamination, regardless of the season.